2010
DOI: 10.1590/s0066-782x2010005000105
|View full text |Cite
|
Sign up to set email alerts
|

Sobrecarga sistólica intermitente promove melhor desempenho miocárdico em animais adultos

Abstract: Background: Corrected transposition of great arteries often evolves with right ventricular dysfunction. The ventricular preparation for anatomic correction in adult patients has produced disappointing results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 33 publications
0
8
0
1
Order By: Relevance
“…According to the authors' experience, the method is useful to follow-up myocardial hypertrophy and failure 31,32,12 . …”
Section: Final Considerationsmentioning
confidence: 99%
“…According to the authors' experience, the method is useful to follow-up myocardial hypertrophy and failure 31,32,12 . …”
Section: Final Considerationsmentioning
confidence: 99%
“…Previous studies have demonstrated a better myocardial performance index for the ventricle subjected to intermittent training. [9,22] Several mechanisms have been proposed to explain the better performance of the ventricle that is intermittently trained. We speculate that it may be associated to the periods of rest and, consequently, to a lesser extent of oxidative process and damage to cardiomyocytes and collagen matrix.…”
Section: Discussionmentioning
confidence: 99%
“…The goats were prepared for the sterile procedure, as described in previous studies [ 11 , 12 ] . For animals in the Traditional group, pulmonary trunk (PT) banding was performed with cardiac tape (Polysuture, São Sebastião do Paraíso, MG), positioned about 10 mm above the valve.…”
Section: Methodsmentioning
confidence: 99%
“…The adult model device was developed in collaboration with SILIMED ( Indústria de silicone e instrumental médico-cirúrgico e hospitalar Ltda. , Rio de Janeiro, RJ), as previously published [ 11 , 12 ] . It has an outer diameter of 24 mm and is 6 mm wide.…”
Section: Methodsmentioning
confidence: 99%